Geochemical, microthermometric, and geochronological characterization of the newly discovered Binnan molybdenum deposit in the great Xing’an Range, northeast China: insights into ore genesis - Qi, Zhongyou; Tian, Shipan; Sun, Guibin; Sun, Gang; Masroor, Alam; Li, Xiaoyu; Du, Bingying (Frontiers in Earth Science, 2025)
In this paper, the Binnan molybdenum (Mo) deposit, a newly discovered deposit located in the Great Xing’an Range, eastern section of the Central Asian Orogenic Belt, has been subjected to a comprehensive integrated study involving field surveys, rhenium-osmium (Re-Os) dating of molybdenite, fluid inclusion analysis, and sulfur-hydrogen-oxygen (S-H-O) isotopic characterization. The mineralization process is divided into three distinct stages: the K-feldspar-quartz stage (I), the quartz-molybdenite stage (II), and the quartz-calcite stage (III). Re-Os isochron dating of molybdenite places the formation of the Binnan Mo deposit during the Late Jurassic, with ages ranging from 142.9 ± 5.1 Ma and 143.7 ± 0.8 Ma. Sulfur isotopic compositions of molybdenite and pyrite, ranging from 1.2‰ to 4.5‰ with a mean of 2.69‰, indicate a magmatic sulfur source of the ore-forming fluids. The hydrogen and oxygen isotopic signatures (δD = −75.5‰ to −92.3‰; δ18O = 13.3‰–15‰) suggest magmatic fluids that progressively mixed with meteoric water during their evolution. Fluid inclusion study indicates that the mineralization temperatures are ranging from 160°C to 380°C. Integrating these findings with previous studies, we infer that the interplay between fluid mixing and temperature variation was critical in precipitating Mo in the Binnan Mo deposit.